Spatial Microsimulation for Rural Policy Analysis - O'Donoghue, Cathal; Ballas, Dimitris; Clarke, Graham; Hynes, Stephen; Morrissey, Karyn; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The aim of this book is to explore the challenges facing rural communities and economies and to demonstrate the potential of spatial microsimulation for policy and analysis in a rural context. This is done by providing a comprehensive overview of a particular spatial microsimulation model called SMILE (Simulation Model of the Irish Local Economy). The model has been developed over a ten year period for applied policy analyis in Ireland which is seen as an ideal study area given its large percentage of population living in rural areas. The book reviews the policy context and the state of the art in spatial microsimulation against which SMILE was developed, describes in detail its model design and calibration, and presents example of outputs showing what new information the model provides using a spatial matching process. The second part of the book explores a series of rural issues or problems, including the impacts of new or changing government or EU policies, and examines the contribution that spatial microsimulation can provide in each area.
1 Introduction -- 2 The Spatial Policy Context of Economic, Agricultural and Environmental Change in Rural Ireland -- 3 A Review of Microsimulation for Policy Analysis -- 4 The SMILE Model: Construction and Calibration -- 5 Validation Issues and the Spatial Pattern of Household Income -- 6 Farm Level Spatial Microsimulation Modelling -- 7 Conservation and Rural Environmental Protection Scheme -- 8 Modelling Greenhouse Gas Emissions from Agriculture -- 9 The Location Economics of Biomass Production for Electricity Generation -- 10 Modelling Farm Viability -- 11 The Spatial Distribution of Household Disposable Income -- 12 Spatial Access to Health Services -- 13 Modelling the Spatial Pattern of Rural Tourism and Recreation -- 14 Conclusions and Next Steps.
Keywords: Economics; Geography; Regional economics; Migration; Economics/Management Science; Regional/Spatial Science; Economic Geography; Migration